A review of gallium phosphide nanophotonics towards omnipotent nonlinear devices - Wang Yifan; Pan Ziyu; Yan Yongxian; Yang Yatao; Zhao Wenhua; Ding Ning; Tang Xingyu; Wu Pengzhuo; Zhao Qiancheng; Li Yi (Nanophotonics)
Gallium phosphide (GaP) has been increasingly prioritized, fueled by the enormous demands in visible light applications such as biomedical and quantum technologies. GaP has garnered tremendous attention in nanophotonics thanks to its high refractive index, indirect bandgap width of 2.26 eV, lattice perfectly matched with silicon, and omnipotent and competitive nonlinear optical properties. Herein, we review the progress and application of GaP in nanoscale devices over the past two decades. The material properties of bulk GaP are first listed, followed by a summary of the methodologies for fabricating nanoscale devices and related integration techniques. Then, we digest the operational mechanisms across different GaP-based devices on their optical linear responses. Following this, we categorize the GaP nonlinear optical effects into multiple aspects including second-harmonic generation, four-wave mixing, Kerr optical frequency combs, etc. Ultimately, we present a perspective on GaP nanophotonics in the context of coexisting and competing modes of various nonlinear effects. We believe that a comprehensive overview of unique GaP will propel these nanophotonic devices toward a mature state, underpinning foundational understanding and leveraging practical innovations.